Derivation of induced pluripotent stem cell lines from New Zealand donors. Issue 1 (1st January 2022) - Oh, Jin Kyo; Przepiorski, Aneta; Chang, Hao-Han; Dodd, Rachel C.; Sander, Veronika; Sorrenson, Brie; Shih, Jen-Hsing; Hollywood, Jennifer A.; de Zoysa, Janak R.; Shepherd, Peter R.; Davidson, Alan J.; Holm, Teresa M.
ABSTRACT: We aimed to generate human induced pluripotent stem cell (iPSC) lines from New Zealand donors. These lines are the first to be generated in New Zealand. Human dermal fibroblasts were collected from two individual donors and reprogrammed with the human OSKM transcription factors using the Sendai virus system. Emerging iPSC colonies were picked, expanded and karyotyped. Clones with normal karyotype were characterised for pluripotency marker expression, p53 mutational status and trilineage differentiation potential. The MANZ-2-2 and MANZ-4-37 iPSC lines showed normal karyotype and expressed pluripotency markers at RNA and protein levels without detectable transgene expression. Both lines differentiated into the three germ layers in vitro and passed the hPSC Scorecard assay for pluripotency and trilineage differentiation. Furthermore, both lines were susceptible to cell apoptosis mediated by nutlin-3a indicative of their wildtype p53 status. This study presents the successful derivation and characterisation of iPSC lines derived from New Zealand donors. These lines will facilitate iPSC-based research in New Zealand and beyond.